Assessing life cycle environmental and economic impacts of building construction solutions with BIM - Carvalho, José Pedro Almeida (2021)
Worldwide authorities are increasingly concerned about construction's efficiency and sustainability, leading to the development of high-performance buildings. However, such facts have shifted a significant percentage of the building life cycle environmental impacts from the operation to the product and construction phases. Thus, the need to evaluate and select more sustainable materials and construction solutions arises, to also minimize impacts from these stages. To evaluate those impacts, LCA and LCC analysis are usually applied to assess the building impacts and costs, through the different life cycle stages. Despite the usefulness of LCA and LCC methods during the project phase, they are usually evaluated in the project later stages. It is too complex and time-consuming to gather and process all the required data during the project early stages. With the recent deployment of BIM, the opportunity to automate and shift LCA and LCC analysis to project early stages stands out. Facing the research gap, this study aims to develop a BIM-based decision-making tool for designers to evaluate the environmental, economic, and functional performance of different building construction solutions. To do so, 18 different simulation scenarios have been created in Autodesk Revit with different combinations of external walls, roofs, and floors. Then, a framework was developed in Dynamo to automatically characterize the building elements life cycle environmental impacts and costs, as well as to automate the LCA and LCC analysis during the project early stages. The outcomes can significantly reduce the required time, errors and efforts when performing LCA and LCC analysis, providing designers with real time decision support data and making an important contribution to the use of BIM for sustainability purposes.